The Peculiarity of Sociographic Knowledge in Hungary - Éva Ale (Acta Universitatis Sapientiae: Social Analysis, 2023)
Hungarian sociography describes society and social problems in an easily understandable way. Sociographic writings do not neglect the political purpose, which creates a specific knowledge about the society within a limited public. Despite the heterogeneity of the genre, the central element of sociographic work is the critique of the dysfunctionality of the existing social system, urging social change. Sociography has not had the conditions to become a science. It remained an area on the border of politics – science – literature. All three at once; however, neither of them. The problem of the institutionalization of sociography means that its importance can be determined through the examination of its task. Burawoy’s theory on public sociology argues that the knowledge of society expressed in scientific language needs to be adapted to the common language. Based on the characteristics of Hungarian sociography, the main goal is to adapt Burawoy’s approach on public sociology to sociography. This article presents the peculiarities of Hungarian sociographic knowledge production and transmission during the 20th century and attempts to place sociography in Burawoy’s system.